Steady state peripheral blood provides cells with functional and metabolic characteristics of real hematopoietic stem cells. Issue 1 (28th March 2017) - Bourdieu, Antonin; Avalon, Maryse; Lapostolle, Véronique; Ismail, Sadek; Mombled, Margaux; Debeissat, Christelle; Guérinet, Marianne; Duchez, Pascale; Chevaleyre, Jean; Vlaski‐Lafarge, Marija; Villacreces, Arnaud; Praloran, Vincent; et al.
Abstract : Hematopoietic stem cells (HSCs), which are located in the bone marrow, also circulate in cord and peripheral blood. Despite high availability, HSCs from steady state peripheral blood (SSPB) are little known and not used for research or cell therapy. We thus aimed to characterize and select HSCs from SSPB by a direct approach with a view to delineating their main functional and metabolic properties and the mechanisms responsible for their maintenance. We chose to work on Side Population (SP) cells which are highly enriched in HSCs in mouse, human bone marrow, and cord blood. However, no SP cells from SSBP have as yet been characterized. Here we showed that SP cells from SSPB exhibited a higher proliferative capacity and generated more clonogenic progenitors than non‐SP cells in vitro. Furthermore, xenotransplantation studies on immunodeficient mice demonstrated that SP cells are up to 45 times more enriched in cells with engraftment capacity than non‐SP cells. From a cell regulation point of view, we showed that SP activity depended on O2 concentrations close to those found in HSC niches, an effect which is dependent on both hypoxia‐induced factors HIF‐1α and HIF‐2α. Moreover SP cells displayed a reduced mitochondrial mass and, in particular, a lower mitochondrial activity compared to non‐SP cells, while they exhibited a similar level of glucose incorporation. These results provided evidence that SP cells from SSPB displayed properties of very primitive cells and HSC, thus rendering them an interesting model for research and cell therapy. Abstract : We provided evidence that Side Population (SP) cells from Steady State Peripheral Blood (SSPB) displayed properties of very primitive cells and HSC based on in vitro and in vivo functional assays. Moreover these SP cells are better maintained during culture at low O2 concentrations, and they displayed a reduced mitochondrial mass and mitochondrial activity compared to non‐SP cells, while exhibiting a similar level of glucose incorporation. These cells are thus an interesting model for research and cell therapy.